2023
DOI: 10.3390/ijms24076202
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Physiological and Transcriptomic Analyses Revealed Improved Cold Tolerance in Cucumber (Cucumis sativus L.) by Exogenous Chitosan Oligosaccharide

Abstract: Cucumber (Cucumis sativus L.), sensitive to cold stress, is one of the most economically important vegetables. Here, we systematically investigated the roles of exogenous glycine betaine, chitosan, and chitosan oligosaccharide in alleviating cold stress in cucumber seedlings. The results showed that 50 mg·L−1 chitosan oligosaccharide had the best activity. It effectively increases plant growth, chlorophyll content, photosynthetic capacity, osmotic regulatory substance content, and antioxidant enzyme activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…In addition, cinnamic acid was rapidly converted to trans-2-hydroxycinnamate under the catalysis of cinnamate 2-hydroxylase, followed by the generation of coumarine through the upregulation of β-glucosidase. Studies have shown that upregulation of PAL , C4H , and 4CL in plants can increase plant tolerance to biotic or abiotic stress [ 49 , 50 ]. Among them, overexpression of PAL has been proven to reduce the level of ROS in Arabidopsis seeds and leaves, increase the activity of POD, CAT, and the content of flavonoids, and reduce the accumulation of MDA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cinnamic acid was rapidly converted to trans-2-hydroxycinnamate under the catalysis of cinnamate 2-hydroxylase, followed by the generation of coumarine through the upregulation of β-glucosidase. Studies have shown that upregulation of PAL , C4H , and 4CL in plants can increase plant tolerance to biotic or abiotic stress [ 49 , 50 ]. Among them, overexpression of PAL has been proven to reduce the level of ROS in Arabidopsis seeds and leaves, increase the activity of POD, CAT, and the content of flavonoids, and reduce the accumulation of MDA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating chitosan oligosaccharide in the study amplified the cold stress response in cucumber seedlings. RNA sequencing data unveiled the expression profiles of CsCCO gene under these conditions [ 33 ]. Notably, genes such as CsNCED6, CsNCED5b, CsNCED5a, CsCCD8, CsCCD7, CsNCED2, CsCCDL-a and CsCCD4b exhibited activation or upregulation in response to cold stress and chitosan oligosaccharide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The expression analysis of all CCO genes to enhance cold tolerance in cucumber was performed by applying chitosan oligosaccharide through a spray method. This analysis utilized previously gathered high-throughput sequencing data [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Soil amendment with chitosan enhanced leaf photosynthesis, leaf biomass, gas exchange, and chlorophyll fluorescence in lettuce [252]. Chitosan application reduced damage caused by cold stress in cucumber seedlings [253]. The application of chitosan and biochar was reported to improve wheat's biochemical, physiological, anatomical, and morphological traits under drought stress [254].…”
Section: Chitosanmentioning
confidence: 99%